The Politics of Language, Discourse, and Identity in the Philippines - Tupas, T, Ruanni F. (Quezon City, 2007)
This volume appeals to scholars from different fields in the ncial sciences and the humanities. From language as a formal system of sounds and signs to discourse as a systemic encoder of meaning and ideology, the essays give us a refreshing range of theoretical and social angles from where we can view the interconnections of language, discourse, identity, and society. This volume is a welcome response to the need for inter- and multi-disciplinary approaches to the central questions of power and nieaning-making.
Keywords: Language and Culture- Philippines; Sociolinguistics- Philippines